The Feminization of Body Work. Issue 1 (19th July 2017) - Cohen, Rachel Lara; Wolkowitz, Carol
Abstract : This article explores the relationship between 'body work' and gender, asking why paid work involving the physical touch and manipulation of others' bodies is largely performed by women. It argues that the feminization of body work is not simply explicable as 'nurturance', nor as the continuation of a pre‐existing domestic division of labour. Rather, feminization resolves dilemmas that arise when intimate touch is refigured as paid labour. These 'body work dilemmas' are rooted in the material nature of body work. They are both cultural (related to the meaning of inter‐corporeality) and organizational (related to the spatial, temporal and labour process constraints of work on bodies). Two sectors are explored as exemplars: hairdressing and care work. Synthesizing UK quantitative data and existing research, the article traces similarities and differences in the composition of these sectors and in how gender both responds to and re‐entrenches the cultural and organizational body work dilemmas identified.